Detection of atoms sputtered from surfaces - Graham, W.G.; Mouncey, S.; Nor, Roslan Md; Wang, L. (Trans Tech Publications, 1995)
The energy distributions of sputtered atoms and ions produced by few hundred to few thousand eV ion bombardment by both atomic and molecular ion beams of polycrystalline and crystalline targets by has been measured. The energy distributions of the ions and atoms are found to be different and quite complex. The distributions provide information about the basic sputtering mechanisms which occur in plasma-surface interactions.